Global Disaggregation of Information-Intensive Services - Apte, Uday M.; Mason, Richard O. (Management Science, 1995)
Information-intensive services are being globally disaggregated as corporations respond to the pressures of increasing global competition, and take advantage of the opportunities made available by the progress of information technology and the emerging global work force. In order to globally disaggregate services, corporations must decide whether or not to carry out a service activity within the organization, and where to locate it, within or outside the geographic boundary of the home-base country. This paper analyzes the opportunities and challenges of global disaggregation of information-intensive services. Specifically, the paper proposes a taxonomy of disaggregation, and develops a theoretical framework that identifies the criteria and guidelines for successfully selecting service activities to be globally disaggregated.